Brightly Luminescent (TbxLu1−x)2bdc3·nH2O MOFs: Effect of Synthesis Conditions on Structure and Luminescent Properties - Viktor G. Nosov; Yulia N. Toikka; Anna S. Petrova; Oleg S. Butorlin; Ilya E. Kolesnikov; Sergey N. Orlov; Mikhail N. Ryazantsev; Stefaniia S. Kolesnik; Nikita A. Bogachev; Mikhail Yu. Skripkin; Andrey S. Mereshchenko (Molecules, 2023)
Luminescent, heterometallic terbium(III)–lutetium(III) terephthalate metal-organic frameworks (MOFs) were synthesized via direct reaction between aqueous solutions of disodium terephthalate and nitrates of corresponding lanthanides by using two methods: synthesis from diluted and concentrated solutions. For (TbxLu1−x)2bdc3·nH2O MOFs (bdc = 1,4-benzenedicarboxylate) containing more than 30 at. % of Tb3+, only one crystalline phase was formed: Ln2bdc3·4H2O. At lower Tb3+ concentrations, MOFs crystallized as the mixture of Ln2bdc3·4H2O and Ln2bdc3·10H2O (diluted solutions) or Ln2bdc3 (concentrated solutions). All synthesized samples that contained Tb3+ ions demonstrated bright green luminescence upon excitation into the 1ππ* excited state of terephthalate ions. The photoluminescence quantum yields (PLQY) of the compounds corresponding to the Ln2bdc3 crystalline phase were significantly larger than for Ln2bdc3·4H2O and Ln2bdc3·10H2O phases due to absence of quenching from water molecules possessing high-energy O-H vibrational modes. One of the synthesized materials, namely, (Tb0.1Lu0.9)2bdc3·1.4H2O, had one of the highest PLQY among Tb-based MOFs, 95%.